2020
DOI: 10.1038/s41597-020-00593-0
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the diversity of magnetotactic bacteria through analysis of open genomic databases

Abstract: Magnetotactic bacteria (MtB) are prokaryotes that possess genes for the synthesis of membranebounded crystals of magnetite or greigite, called magnetosomes. Despite over half a century of studying MTB, only about 60 genomes have been sequenced. Most belong to Proteobacteria, with a minority affiliated with the Nitrospirae, Omnitrophica, Planctomycetes, and Latescibacteria. Due to the scanty information available regarding MTB phylogenetic diversity, little is known about their ecology, evolution and about the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 85 publications
0
48
0
Order By: Relevance
“…However, over the past decade, our knowledge of MTB diversity has been significantly expanded through the applications of cultivation-dependent and -independent approaches (Kolinko et al, 2012;Bazylinski et al, 2013;Lefèvre and Bazylinski, 2013;Lin et al, 2017a;Amor et al, 2020b). MTB have thus far been identified in at least 16 phylum-level lineages (Lin et al, 2018(Lin et al, , 2020bUzun et al, 2020), suggesting unexpected taxonomic diversity of magnetosome biogenesis and magnetotaxis across the domain Bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, over the past decade, our knowledge of MTB diversity has been significantly expanded through the applications of cultivation-dependent and -independent approaches (Kolinko et al, 2012;Bazylinski et al, 2013;Lefèvre and Bazylinski, 2013;Lin et al, 2017a;Amor et al, 2020b). MTB have thus far been identified in at least 16 phylum-level lineages (Lin et al, 2018(Lin et al, , 2020bUzun et al, 2020), suggesting unexpected taxonomic diversity of magnetosome biogenesis and magnetotaxis across the domain Bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetotactic bacteria phylogenetically affiliated within the Nitrospirae phylum are of great interest because of their biomineralization of up to several hundreds of Fe 3 O 4 magnetosomal crystals and formation of dozens of sulfur globules in a single cell, linking these microorganisms to the key steps of iron and sulfur cycling in aquatic ecosystems (Spring et al, 1993;Jogler et al, 2010;Lin et al, 2014b;Li et al, 2020). Historically, Nitrospirae MTB have only been discovered in freshwater environments (Spring et al, 1993;Flies et al, 2005;Amann et al, 2006); however, recent studies have revealed that these MTB are globally distributed in a wider range of environments than anticipated previously, including hot springs (Lefèvre et al, 2010;Uzun et al, 2020), estuary and marine ecosystems (Lin et al, 2017a;Qian et al, 2019), and acidic peatlands (Lin et al, 2020b). Due to the lack of cultivated representatives, much of our understanding of Nitrospirae MTB was obtained through 16S rRNA gene-based methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomes of many MTB species were sequenced [20,21,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60], and genes specific for magnetotactic bacteria were found, which control the magnetosome formation [61,62]. These genes are located in a so-called magnetosome genomic cluster (MGC) and are responsible for the formation of the magnetosome membrane, transport of iron into magnetosomes, nucleation and growth of magnetite crystals, and the shape and size of the latter [17,[63][64][65][66][67][68][69].…”
Section: Mtb and Magnetosomesmentioning
confidence: 99%
“…Morphologically, MTB are diverse including vibrions, rods, cocci, spirilla, and so-called "multicellular" organisms [17]. According to their present phylogenetic position, MTB are classified in the following phyla: Proteobacteria, Nitrospirota, Omnitrophota, Latescibacterota, Planctomycetota, Nitrospinota, Hydrogenedentota, Elusimicrobiota, Fibrobacterota, Riflebacteria, Bdellovibrionota, UBA10199, Desulfobacterota [18][19][20][21] (Figure 2). Only a few MTB strains were isolated into a pure culture.…”
Section: Introductionmentioning
confidence: 99%